Red mud/steel slag three-dimensional electrochemical system for the removal of organic pollutant with Na2S2O3 as electrolyte: Contribution of •OHads - Han, Yi; Guo, Mengxin; Shi, Ting; Wang, Zhipeng; Wang, Yi; Xu, Zhibing; Wang, Dejin; Gao, Hongcheng; Peng, Zheng; Hou, Haobo (Separation and purification technology, 2025)
[Display omitted] •Red mud and steel slag three-dimensional electrodes efficiently degrade TCH effectively.•Na2S2O3 electrolyte optimizes the Fe2+/Fe3+ cycle and expanding the pH range of applicability.•The presence of Na2S2O3 prevents iron dissolution, maintaining high degradation efficiency.•This approach demonstrates significant efficacy in the treatment of various industrial wastewaters. The dynamic changes in the iron redox cycle (Fe2+/Fe3+) played a crucial role in the electro-Fenton degradation of organic pollutants. The synthesis of composite particle electrodes RMSSx:y from a mixture of steel slag (SS) and red mud (RM) was applied in a three-dimensional electrochemical system for the remediation of hydrochloric tetracycline (TCH) in wastewater, utilizing Na2S2O3 as an electrolyte. Further, some investigations were conducted to determine the effects of RM/SS, electrolyte, particle electrode dosage, cell voltage, and pH on TCH degradation efficiency. Under optimal conditions such as 8 g/L RMSS5:5 particle electrodes, a cell voltage of 4 V, an initial pH of 3, and 6 mM Na2S2O3 electrolyte, the degradation rate of TCH in wastewater was 98.3 %. Meanwhile, its total organic carbon (TOC) was reduced by 88 % within 60 min. Cyclic experiments with consistently high degradation efficiency demonstrated the stability of the particle electrode RMSS5:5. The practical applicability of RMSS5:5 was further confirmed through its successful treatment of various industrial wastewaters, including dyeing (DW), chemical (CW), and pharmaceutical (PW) effluents, achieving chemical oxygen demand (COD) removal rates of 67.8 %, 67.6 %, and 65.0 % respectively. The enhancement of TCH degradation through the utilization of Na2S2O3 as the electrolyte was primarily attributed to the complexation and reduction effects exerted by S2O32- ions. These effects prevented the leaching and precipitation of iron ions, facilitated the reduction of Fe (III), and consequently enabled •OHads to play a dominant role in the degradation process. These findings demonstrated the potential of RMSS5:5 in efficiently degrading emerging contaminants, thereby offering an innovative approach for utilizing SS and RM as functional materials in electro-Fenton processes.